GAP-43 closely interacts with BDNF in hippocampal neurons and is associated with Alzheimer's disease progression - Lee, Ye Ji; Jeong, Ye Ji; Kang, Eun Ji; Kang, Beom Seok; Lee, Song Hee; Kim, You Jin; Kang, Seong Su; Suh, Sang Won; Ahn, Eun Hee (Frontiers in Molecular Neuroscience, 2023)
Abstract Growth-associated protein 43 (GAP-43) is known as a neuronal plasticity protein because it is widely expressed at high levels in neuronal growth cones during axonal regeneration. GAP-43 expressed in mature adult neurons is functionally important for the neuronal communication of synapses in learning and memory. Brain-derived neurotrophic factor (BDNF) is closely related the neurodegeneration and synaptic plasticity during the aging process. However, the molecular mechanisms regulating neurodegeneration and synaptic plasticity underlying the pathogenesis and progression of Alzheimer's disease (AD) still remains incompletely understood. Remarkably, the expression of GAP-43 and BDNF perfectly matches in various neurons on the Human Brain Atlas Database. Moreover, GAP-43 and BDNF are highly expressed in the healthy adult hippocampus brain region and inversely correlate with the Amyloid beta (Aβ), which is the pathological peptide of the amyloid plaques found in the brains of AD patients. This data led us to investigate the impact of the direct molecular interaction between GAP-43 and BDNF in hippocampal neuron fate. Here we show that GAP-43 and BDNF are inversely associated with pathological molecules for AD (Tau and Aβ). In addition, we define the three-dimensional protein structure for GAP-43 and BDNF, including the predictive direct binding sites via the analysis of ClusPro 2.0, and demonstrate that the deprivation of GAP-43 and BDNF triggers hippocampal neuronal death and memory dysfunction employing the GAP-43 or BDNF knock-down cellular and animal models. These results present that the GAP-43 and BDNF are direct binding partners in hippocampal neurons and their molecular signaling might be the potential therapeutic target for AD.